Development of Fikih Learning Module at Madrasah Tsanawiyah: An Inclusive Approach - Nur Cholid; Suariyati, Suariyati; Putri, Linda Indiyarti (Jurnal Pendidikan Agama Islam, 2021)
The development of learning modules is a solution to the problems faced by teachers when delivering material to students in class. This study aims to develop Fikih learning tools with an inclusive approach that can be applied in Madrasah Tsanawiyah. In addition, this study also aims to determine whether the learning module product developed is commercially feasible or not. This research is a research and development (Research and Development). In the design validation stage, the class VII Fikih learning tools with the inclusion approach were validated by two material experts and two media experts. The data collection technique is in the form of a questionnaire instrument. The data from the validation results were then converted to a Likert scale. The results showed that Fikih learning tools with an inclusive approach validated by material and media experts had very good quality content of the material (with a value of 4.35), the quality of presentation of the material was very good (with a value of 4.52), these results were obtained after testing second stage, while the quality of media graphics is very good (with a score of 4.53) and the quality of media language is very good (with a value of 4.33). And the results of the trial there was an increase in the average post-test to the pre-test by 17.5 or 29.02%. These results indicate that the Fikih learning tool with the inclusion approach that was developed is feasible to use as a reference for learning tools.